GAMBARAN PEMERIKSAAN CERVICAL RIGHT POSTERIOR OBLIQUE MENGGUNAKAN CENTRAL RAY TEGAK LURUS DAN 15O CHEPALAD PADA KASUS CERVICAL ROOT SYNDROME - Sri Sugiarti (Health Care Media, 2019)
Cervical Right Posterior Oblique radiographic examination technique is one of the examination techniques that aims to determine the overall picture of cervical anatomy, one of the most common cases in cervical patients is cervical root syndrome. Cervical root syndrome is a condition caused by irritation or suppression of nerve roots. The choice of central ray by cornering an x-ray tube or horizontally perpendicular to working on an examination is very important to the results of the examination. The research was carried out at the Radiology Installation in the general hospital area of Dr.R. Soedarsono Pasuruan. In this study several preparations were made to support cervical examination with a central ray of 15 ° cephalad and perpendicular central ray in patients with cervical root syndrome. In this study the tools that will be used as supporting examinations include X- ray planes, Cassettes (Computer Radiography Image Plate), Image plate readers, and Laser printers. In the cervical RPO (Right Posterior Oblique) radiographic examination using a 15 ° cephalad angle, the results of the intervertebral foramen radiograph appear clearer and longer. While the radiographic examination without angulation shows that the results of the intervertebral foramen radiograph are more narrow.